Chronotope au féminin: L'émergence d’une parole féminine dans la littérature épistolaire au siècle des Lumières - Vykypělová, Klára (Verbum – Analecta Neolatina, 2014)
Women’s individuality is still an open question that attracts attention. We can look for women’s emancipation because of the efforts for recognition of the woman as a free individuality gifted with reason. This fact becomes an especially interesting dimension in the literature. The aim of this paper is to highlight the interdependence of the individual and society in the 18th century, and how this relationship is reflected in literary works. We will discuss the connection of two methodological concepts:Mikhail Bakhtin’s concept of the chronotope and Michel Foucault’s concept of identity. These two concepts will be furthermore applied to the epistolary novel Lettres d’une Péruvienne (1747), written by Françoise de Graffigny.